2018
DOI: 10.1016/j.jclepro.2018.02.276
|View full text |Cite
|
Sign up to set email alerts
|

Locally produced lactic acid bacteria for pathogen inactivation and odor control in fecal sludge

Abstract: Providing safe fecal sludge (FS) sanitation has remained an important goal of global communities because of the high risks imposed on human health of the exposure to un-sanitized FS. This study used lactic acid fermentation as a pre-treatment technology to evaluate the sanitization effect of lactic acid bacteria (LAB) on FS. A combination of fermented rice flour and brown sugar was used as the medium to prepare LAB, and fecal coliforms were used as the indicator organisms. The addition of a LAB suspension grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Sufficient production of lactic acid and sustained acidity are key factors for the LAF process and elimination of pathogens (Odey et al 2018b ). In this study, lactic acid was not measured, and it was not possible to monitor the pH as little or no leachate was produced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sufficient production of lactic acid and sustained acidity are key factors for the LAF process and elimination of pathogens (Odey et al 2018b ). In this study, lactic acid was not measured, and it was not possible to monitor the pH as little or no leachate was produced.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly though, in 7 F, the E. coli numbers were approximately 5 log 10 lower than in 7 C and 7 CB. LAF has been shown to efficiently reduce fecal indicator bacteria (Anderson et al 2015 ; Andreev et al 2017 ; Odey et al 2018b ). However, it has not been extensively researched whether LAF has a specific effect on fecal pathogens, nor whether the reduction in the indicator organisms is related to a reduction in other relevant pathogens like Salmonella, Ascaris sp., and viruses.…”
Section: Discussionmentioning
confidence: 99%
“…A promising application of biological disinfection is lactic acid fermentation of fecal sludge with fermented food wastes. Odey et al (2018) reported an effective inactivation of FC and E. coli using fermented rice flour and fermented milk, respectively. A laboratory-scale experiment demonstrated a Log 4, Log 5.5 and Log 7.5 reduction in total coliform concentration in fecal sludge after 21 days using a non-specified microbial culture (EM4) as the inoculum and 0, 5 and 10% (w/w) glucose as the substrate (Soewondo et al 2014).…”
Section: Chemical and Biological Disinfectionmentioning
confidence: 99%
“…As a result, the chemical disinfection using chlorine and lime, pit latrine additives using Ikati and Soda and peat liners for pit latrines have the highest score, likely attributed to their robustness as a technology in wastewater management. On the contrary, AD adopted pit latrines byRao et al (2018), solar technology or SIDRO toilets adopted byRedlinger et al (2001), lactic acid fermentation technology byOdey et al (2018) and hydrophobic membrane lined toilets proposed byMarzooghi et al (2017) had the lowest scores. Although the scoring method inevitably works in favor of robust technologies versus developing, field-scale technologies, it serves to highlight the areas of a technology still facing challenges to gain market acceptability and user adoption as a stand-alone in situ treatment system.…”
mentioning
confidence: 98%
“…Step 3: Multi-Dimensional Sustainability Assessment Analysis of the interviews with local stakeholders revealed several sustainability criteria of importance for nutrient recycling from Composting* X X X X Strauss et al, 2003;Strande et al, 2014;Komakech et al, 2015 Vermicomposting* X X X X Strande et al, 2014;Komakech et al, 2015;Bhat et al, 2018 Fly larvae composting* X X X X Strande et al, 2014;Komakech et al, 2015 Anaerobic treatment X X X Diener et al, 2014;Strande et al, 2014 Lactic acid fermentation X X X X Anderson et al, 2015;Andreev, 2017;Odey et al, 2018 Productive wetland X X X Koottatep et al, 2005;Strande et al, 2014 Algae production X X Grobbelaar, 2004;Barbera et al, 2018 Aquaculture X X Strande et al, 2014 Microbial fuel cells X X Raheem et al, 2018;Lu et al, 2019;Palanisamy et al, 2019 Chemical Precipitation X X X Shiba and Ntuli, 2017;Chapeyama et al, 2018;Tarragó et al, 2018;Li et al, 2019 Stripping and capture X Harder et al, 2019…”
Section: Nutrient-enriched Sorbent Materialsmentioning
confidence: 99%